Validation of Modified Hertel Exophthalmometer. Issue 3 (September 2021) - Jamal, Rizwana Fathima; Azariah, Emmanuel; Pandyan, Deepak; Chinnaswami, Ravindran
Study Design: This is a correlation study. Objective: The objective was to obtain normative values from modified Hertel exophthalmometer, to compare difference in values between modified and standard Hertel exophthalmometer and to statistically analyze for correlation. Methods: The study to validate the modification done to Hertel exophthalmometer was performed at the Department of Oral and Maxillofacial Surgery at our institute. Informed consent was obtained from patients; measurement in 100 volunteers was made with Hertel and modified Hertel exophthalmometer by a single observer, and the measurements taken by the 2 devices were tabulated along with variables such as age and gender. Data were collected and statistical analysis was performed to compare and correlate the values between standard and modified exophthalmometer. Differences of ocular protrusion values in gender and age were also calculated. Results: There has been no statistically significant difference in the normative data between standard Hertel and modified Hertel exophthalmometer and in relation to age and gender. Conclusions: The modification of the Hertel exophthalmometer is validated and can also be used for relative exophthalmometry to assess the need for treatment and to evaluate the globe position and orbital volume intraoperatively. The proposed modification of the instrument allows it to be used in cases when one of the lateral orbital walls is fractured or displaced due to trauma.